A titanium(iii) phosphite exhibits polymorph-distinct redox activity involving proton-coupled electron transfer. Issue 53 (10th June 2021) - Hung, Ling-I; Hsieh, Tsung-Hsiu; Syu, Jhao-Yang; Chen, Pei-Lin; Lin, Chia-Her; Wang, Sue-Lein
Abstract : A Ti III phosphite, possessing two polymorphs with different redox activities, exhibits a complete cycle of PCET reactions starting from Ti III to Ti IV via oxidation with H2 release, and back to Ti III via photoreduction involving external e − /H + . Abstract : A novel titanium(iii ) phosphite with intriguing polymorphism and solid-state proton-coupled electron transfer (PCET) oxidation is presented. The polymorphs show structure-dependent PCET reactivity, interpretable by proton distribution in channels. Combined with subsequent photoreduction, the redox cycle initiated with Ti III can produce H2 and transform organics.